Therapeutic Potential of Stem Cells from Human Exfoliated Deciduous Teeth in Models of Acute Kidney Injury. - Yuka Hattori; Hangsoo Kim; Naotake Tsuboi; Akihito Yamamoto; Shinichi Akiyama; Yiqin Shi; Takayuki Katsuno; Tomoki Kosugi; Minoru Ueda; Seiichi Matsuo; Shoichi Maruyama (PLoS ONE, 2015)
Acute kidney injury (AKI) is a critical condition associated with high mortality. However, the available treatments for AKI are limited. Stem cells from human exfoliated deciduous teeth (SHED) have recently gained attention as a novel source of stem cells. The purpose of this study was to clarify whether SHED have a therapeutic effect on AKI induced by ischemia-reperfusion injury.The left renal artery and vein of the mice were clamped for 20 min to induce ischemia. SHED, bone marrow derived mesenchymal stem cells (BMMSC) or phosphate-buffered saline (control) were administered into the subrenal capsule. To confirm the potency of SHED in vitro, H2O2 stimulation assays and scratch assays were performed.The serum creatinine and blood urea nitrogen levels of the SHED group were significantly lower than those of the control group, while BMMSC showed no therapeutic effect. Infiltration of macrophages and neutrophils in the kidney was significantly attenuated in mice treated with SHED. Cytokine levels (MIP-2, IL-1β, and MCP-1) in mice kidneys were significantly reduced in the SHED group. In in vitro experiments, SHED significantly decreased MCP-1 secretion in tubular epithelial cells (TEC) stimulated with H2O2. In addition, SHED promoted wound healing in the scratch assays, which was blunted by anti-HGF antibodies.SHED attenuated the levels of inflammatory cytokines and improved kidney function in AKI induced by IRI. SHED secreted factors reduced MCP-1 and increased HGF expression, which promoted wound healing. These results suggest that SHED might provide a novel stem cell resource, which can be applied for the treatment of ischemic kidney injury.